2017
DOI: 10.1002/asl.736
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of peat humification, magnetic susceptibility and trace elements of Hani peatland, northeastern China: paleoclimatic implications

Abstract: A high-resolution peat humification record is obtained from Hani peatland, northeastern China to study climate change. An absorbance value time series from alkali-extraction is used as a peat humification indicator. In addition, Hani peat magnetic susceptibility and trace elements have also been investigated. There is a sensitive response to abrupt climate changes when comparing a high-resolution peat humification record with a Hani 18 O temperature proxy record and a drift ice record from the North Atlantic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Peat humification-climate researches have been mostly undertaken in North Europe (Amesbury et al, 2012; Borgmark and Wastegård, 2008; Vorren et al, 2012), East Asia (Hong et al, 2001; Ma et al, 2008; Wang et al, 2004; Xiao et al, 2017), North America (Payne and Blackford, 2008), Australia and New Zealand (Burrows et al, 2014; Jara et al, 2017; Newnham et al, 2019; Viau and Gajewski, 2009; Wilmshurst et al, 2002). In Central Asia, the work of peatland research gained more international recognition in recent decades due to several high-resolution alpine ombrotrophic peatlands (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peat humification-climate researches have been mostly undertaken in North Europe (Amesbury et al, 2012; Borgmark and Wastegård, 2008; Vorren et al, 2012), East Asia (Hong et al, 2001; Ma et al, 2008; Wang et al, 2004; Xiao et al, 2017), North America (Payne and Blackford, 2008), Australia and New Zealand (Burrows et al, 2014; Jara et al, 2017; Newnham et al, 2019; Viau and Gajewski, 2009; Wilmshurst et al, 2002). In Central Asia, the work of peatland research gained more international recognition in recent decades due to several high-resolution alpine ombrotrophic peatlands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of proxies have been used to reconstruct the regional paleoclimatic changes (e.g. Feng et al, 2017; Rao et al, 2019, 2020; Xiao et al, 2017; Yang et al, 2019; Zhang et al, 2018a, 2018b) and the related proxies mainly include pollen assemblages (Feng et al, 2017; Wang and Zhang, 2019; ; Zhang et al, 2020a, 2020b, 2020c), stable isotopes of plant macrofossils (Rao et al, 2019, 2020; Yang et al, 2019; Zhang et al, 2018c) and n-alkane compositions (Wu et al, 2020; Zhang et al, 2016). However, the importance and implication of peat humification in the southern Altai Mountains are not in-depth investigated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the amount of mineral matter in peat is strongly interrelated with humification processes (Tolonen, 1984). Due to mass loss of organic matter in peat bogs in the course of proceeding decomposition during drier periods (see also Huang et al, 2013;Xiao et al, 2017), an enrichment of mineral matter per volume unit takes place, resulting in an increase in the ash content (Boelter, 1969). This, in turn, might improve nutrient availability and could lead to a positive feedback on microbial decomposition of peat (Kempter, 1996).…”
Section: Climate-driven Interrelations Of Peat Proxiesmentioning
confidence: 99%
“…Tolonen, 1984;Kempter, 1996;Martínez Cortizas et al, 2007;Engel et al, 2010;Leifeld et al, 2011;Drzymulska, 2016). However, a direct linkage between higher ash contents and warmer climate conditions causing slower growth rates and higher mineralization rates (see also Sîre et al, 2008;Huang et al, 2013;Xiao et al, 2017) does not always hold up to scrutiny, as Stivrins et al (2017) imply by underlining the capacity of peat bogs to buffer climate variations. This is further aggravated by the fact that, from a climatological perspective, no stable relationship between temperature and precipitation exists (Bell et al, 2018).…”
Section: Climate-driven Interrelations Of Peat Proxiesmentioning
confidence: 99%
“…Hani peatland in Jilin Province of northeast China is one of the few peatlands that remain wellpreserved (C. Schroder et al, 2007). It is situated at the frontal area of the EASM and previous studies have shown that past environmental changes can be reconstructed from pollen, grain size, stable isotopes as well as elemental and organic indicators (Ficken et al, 2000;Zhou et al, 2010;Hong et al, 2005Hong et al, , 2009Hong et al, 2010;Seki et al, 2009;McClymont et al, 2010;Yamamoto et al, 2010;Zheng et al, 2010Zheng et al, , 2011aZheng et al, , b, 2017Zheng et al, , 2018Huang et al, 2013;Wu et al, 2016;Li et al, 2017;Xiao et al, 2017), but its development history, and regional hydrology due to climate changes can still be further elaborated. For example, some records suggest that the precipitation in Hani decreased from the early to late Holocene (Hong et al, 2010;Hong et al, 2009Hong et al, , 2010 while some others suggest it increased gradually (Zheng et al, 2018).…”
mentioning
confidence: 99%